2020
DOI: 10.1186/s12879-020-05405-9
|View full text |Cite
|
Sign up to set email alerts
|

Trends and epidemiological analysis of hepatitis B virus, hepatitis C virus, human immunodeficiency virus, and human T-cell lymphotropic virus among Iranian blood donors: strategies for improving blood safety

Abstract: Background Blood transfusion is associated with potential risks of transfusion-transmitted infections (TTIs). Different strategies are needed to monitor blood safety and screen the donors’ efficacy, such as evaluation of the prevalence and trends of TTIs. This study was conducted to evaluate the prevalence and trends of TTIs, including hepatitis B virus (HBV), hepatitis C virus (HCV), human immunodeficiency virus (HIV), and human T-cell lymphotropic virus (HTLV 1/2), and the impact of the donors’ characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…However, over time, no change was observed in the HTLV-1 infection rate among the general population of Razavi Khorasan province [21,26,30]. Statistically significant higher rates of HTLV-1 infection were reported in Iranian females as compared to males [30][31][32]41,42,[44][45][46]51]. In that sense, a recent meta-analysis estimated a three-fold higher infection rate among female blood donors as compared to male donors (0.64%, 95% CI: 0.13-3.01% and 0.20%, 95% CI: 0.15-0.27%, respectively) [63].…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…However, over time, no change was observed in the HTLV-1 infection rate among the general population of Razavi Khorasan province [21,26,30]. Statistically significant higher rates of HTLV-1 infection were reported in Iranian females as compared to males [30][31][32]41,42,[44][45][46]51]. In that sense, a recent meta-analysis estimated a three-fold higher infection rate among female blood donors as compared to male donors (0.64%, 95% CI: 0.13-3.01% and 0.20%, 95% CI: 0.15-0.27%, respectively) [63].…”
Section: Resultsmentioning
confidence: 92%
“…Regular screening of all donated blood units for antibodies against HTLV-1/2 followed by confirmatory tests was introduced in northeastern Iran in 1995 [64] and then extended to some provinces in the north and northwest parts of the country. These tests were performed among first-time and regular blood donors, and as a result, many surveys revealed a gradual decrease in HTLV-1 prevalence among Iranian blood donors from 0.13% in 2009 to 0.03% in 2018 (Table 1) [31,32,63]. A declining trend in the infection rate among blood donors was documented in Razavi Khorasan [41,42,45,47] as well as other provinces of Iran [48,51].…”
Section: Resultsmentioning
confidence: 99%
“…This population-based study [4] , comprising 5,533 screened individuals, reported a 4% HBV prevalence and a 2.8% prevalence among HBsAg-positive individuals for HDV, which is similar or slightly lower than our estimate of 3.37% in blood donors. In general, in Turkey and other neighboring countries such as Iran, the HBV prevalence data from blood donors are considered, to some extent, ambiguous because they may underestimate the HBV burden in the region because high-risk groups for HBV/HDV are rejected from blood donation without pre-transfusion HBsAg assessment [16 , 17] . Blood donation in Turkey is on a voluntary basis and assessment of high-risk groups is done through a detailed questionnaire before blood donation.…”
Section: Discussionmentioning
confidence: 99%
“…Blood donation sessions, therefore, provide almost no opportunity for potential HTLV‐1 carriers to self‐select and avoid blood donation in relation to subjective symptoms. Surveys of HTLV‐1 seroprevalence targeting a large number of blood donors have thus been conducted around the world 15–18 . However, it has been well recognized that blood donors in almost all countries of the world are not always representative of the general population of that country, particularly with respect to bloodborne viruses (“healthy donor effect”) 19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…Surveys of HTLV-1 seroprevalence targeting a large number of blood donors have thus been conducted around the world. [15][16][17][18] However, it has been well recognized that blood donors in almost all countries of the world are not always representative of the general population of that country, particularly with respect to bloodborne viruses ("healthy donor effect"). 19,20 A survey of a hospital-based population in Nagasaki prefecture in Japan, which is endemic for HTLV-1, yielded a 50% higher prevalence than that reported from blood donor screening.…”
Section: Estimated Number Of Carriersmentioning
confidence: 99%